Explore Westonci.ca, the premier Q&A site that helps you find precise answers to your questions, no matter the topic. Get detailed answers to your questions from a community of experts dedicated to providing accurate information. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
5 + (n - 1)²
5 + (n - 1)(n - 1)
5 + (n² - n - n + 1)
5 + (n² - 2n + 1)
n² - 2n + 1 + 5
n² - 2n + 6 = 0
n = -(-2) +/- √((-2)² - 4(1)(6))
2(1)
n = 2 +/- √(4 - 24)
2
n = 2 +/- √(-20)
2
n = 2 +/- 2i√(5)
2
n = 1 + i√(5)
n = 1 + i√(5) n = 1 - i√(5)
The answer is equal to B.
5 + (n - 1)(n - 1)
5 + (n² - n - n + 1)
5 + (n² - 2n + 1)
n² - 2n + 1 + 5
n² - 2n + 6 = 0
n = -(-2) +/- √((-2)² - 4(1)(6))
2(1)
n = 2 +/- √(4 - 24)
2
n = 2 +/- √(-20)
2
n = 2 +/- 2i√(5)
2
n = 1 + i√(5)
n = 1 + i√(5) n = 1 - i√(5)
The answer is equal to B.
Thanks for stopping by. We are committed to providing the best answers for all your questions. See you again soon. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.